PIMT is a novel and potent suppressor of endothelial activation - Zhang, Chen; Guo, Zhi-Fu; Liu, Wennan; Kazama, Kyosuke; Hu, Louis; Sun, Xiaobo; Wang, Lu; Lee, Hyoungjoo; Lu, Lin; Yang, Xiao-Feng; Summer, Ross; Sun, Jianxin (eLife, 2023)
Proinflammatory agonists provoke the expression of cell surface adhesion molecules on endothelium in order to facilitate leukocyte infiltration into tissues. Rigorous control over this process is important to prevent unwanted inflammation and organ damage. Protein L-isoaspartyl O-methyltransferase (PIMT) converts isoaspartyl residues to conventional methylated forms in cells undergoing stress-induced protein damage. The purpose of this study was to determine the role of PIMT in vascular homeostasis. PIMT is abundantly expressed in mouse lung endothelium and PIMT deficiency in mice exacerbated pulmonary inflammation and vascular leakage to LPS(lipopolysaccharide). Furthermore, we found that PIMT inhibited LPS-induced toll-like receptor signaling through its interaction with TNF receptor-associated factor 6 (TRAF6) and its ability to methylate asparagine residues in the coiled-coil domain. This interaction was found to inhibit TRAF6 oligomerization and autoubiquitination, which prevented NF-κB transactivation and subsequent expression of endothelial adhesion molecules. Separately, PIMT also suppressed ICAM-1 expression by inhibiting its N-glycosylation, causing effects on protein stability that ultimately translated into reduced EC(endothelial cell)-leukocyte interactions. Our study has identified PIMT as a novel and potent suppressor of endothelial activation. Taken together, these findings suggest that therapeutic targeting of PIMT may be effective in limiting organ injury in inflammatory vascular diseases.
Keywords: inflammation; acute lung injury; endothelium; post-translational modification